Kinetics and Mechanism of the Thermal Decomposition Reaction of 3,6-diphenyl- 1,2,4,5-tetroxane in 2-methylcellosolve Solution - G. Bordon, Alexander; I. Profeta, Mariela; M. Romero, Jorge; L. Jorge, Nelly; A. Castro, Eduardo (Current Organic Synthesis, 2014)
3,6-diphenyl-1,2,4,5-tetraoxane(DFT) has been prepared in order to study the effect of temperature on the reaction kinetics in methylcellosolve solution. The thermolysis reaction fulfills a kinetic law of the first order up to conversions approximately 60 % of the DFT. The values of ΔH#=20.2±1.0 kcal mol-1 and ΔS#= -25.3±1.4 cal mol-1 K-1 of the rupture of one O-O bond in the diperoxide molecule were obtained by measuring the remanent diperoxide at different reaction times by GC technique. Benzaldehyde and benzoic acid were detected by GC as the major organics products of the reaction.
Keywords: tetroxane